Fuzzy Logic-based PI Controller with PWM for Buck-Boost Converter - Al-Dabbagh, Zainab Ameer; Shneen, Salam Waley; Hanfesh, Abduljabbar O. (Journal of Fuzzy Systems and Control, 2024)
Electronic power converters have emerged and been widely used as a result of the use of direct current systems, and one of their most important uses is renewable energy such as solar energy. When electrical energy is generated from primary sources such as solar energy, converters can be added to convert to a higher or lower value using a buck-boost converter. If the converter is used and operated within an open-loop system, which is the first proposed test case, it is possible to verify the ability of the converter to convert with a constant current rate according to its function, but it turns out that the conversion, in this case, is in a state of instability, which requires work to add feedback and make the system operate in a system Closed loop is the second test case to reach and ensure a stable state for the system. To ensure the scheduled effort, work is being done to improve the system by adding traditional and expert controllers. Thus, by adjusting the parameters of the controller, acceptable performance can be obtained. It represents a transformer with a controller that maximizes results with accuracy and stability. The controller works to track errors through a sensor. It shows the output value with the appropriate reference value for the transformer output, in addition to the presence of a comparator that detects the error to be an input for the controller, which works according to a working algorithm to implement a compensation state, treat the error and instability, get rid of the deviation, and return to the stable state. Various control methods are implemented to improve performance, including traditional PI and expert Fuzzy, with the best being determined by comparing the system output results, as the simulation showed the superiority of fuzzy logic over traditional in terms of response speed time, rise time, and under and over bypass rates.